Functions of Indirectness in American Idol Judges Comments - Raynesta Mikaela Indri Malo (Universitas Sanata Dharma, 2016)
Indirectness is one of the most efficient ways to communicate each other. People useindirectness in communication for different purposes. The most discussed and discovered purposeacross cultures is for politeness; people use language in indirect way to prevent hurting othersfeelings. In many cultures, indirectness is highly valued because saving face and harmony in socialrelationships are highly respected. This study is a descriptive study which is aimed at analyzing thefunctions or the purpose of using indirectness or indirect language in one of the rarely discussedrealm of language use, a TV show, specifically, American Idol. The findings also reveal the strategiesused in order to perform the functions. The data is limited to the audition of American Idol seasoneight (8) which was held in 2009. There were 7 recordings for the 8 cities of audition. The totalnumber of data used in this study was 50 indirect comments. The result shows that there were 3functions of the use of indirectness in the comments of the judges. The functions were (i) being ironic,(ii) being polite, and (iii) giving hints.Keywords: indirectness, politeness, judges comments